O DEMONÍACO EM MARCOS 3,20-35 - Cardoso, Regina Aparecida Lourenço (2015)
The ancient thought had interpreted all harmful events or personal and psychological illnesses as satanic influence. Regarding this background the purpose of this work is to analyze the imagery of Markan community concerning the demonic and how this reading would have impacted the lives of people in that context. In order to carry this out we shall seek to identify, in the passage of Mark 3.20-35, demonic mechanisms of that society and how this imaginary was reflected in the community quotidian. In addition we shall verify the reason why the practices of Jesus involving exorcism caused such a disconfort, leading to his identification as a demon. We regard as necessary to evaluate the thaumaturgical activity of Jesus and its representativeness at the time, as well as the social effect it produced and its reception by Markan community.